Transitivity of Spanish perception verbs: a gradual category? - Enghels, Renata (Borealis – An International Journal of Hispanic Linguistics, 2013)
This article examines to what extent perception verbs occurring in a syntactically transitive scheme are also semantically transitive. Indeed, since the perception process represents a mental rather than a physical contact between the perceiver/subject and the stimulus/object, it should be distinguished from the prototypical transfer of energy. It is shown that the semantic and conceptual differences between the perception modalities influence on the linguistic behaviour of Spanish perception verbs. In this perspective, the verbs ver (to see), oír (to hear), mirar (to look at) and escuchar (to listen to) are ranged on a scale of transitivity. The validity of the elaborated hierarchy of transitivity is verified by means of empirical data. Based on a large corpus of infinitive constructions, it will be examined to what extent the position of a perception verb on the scale of transitivity correlates with the preferred case markings of its stimulus/object. A specific morphosyntactic phenomenon is studied, namely the special marking of the DO by the prepositional accusative.